A novel path for carbon-rich resource utilization with lower emission and higher efficiency: An integrated process of coal gasification and coking to methanol production. (15th June 2019) - Chen, Jianjun; Yang, Siyu; Qian, Yu
Abstract: Coal gasification, the major approach to coal-based chemicals synthesis, suffers from substantial carbon dioxide emission. Reducing CO2 emission is the emphasis and hotspot in coal chemical industry. On the other hand, the traditional coking process is inefficiency of carbon and hydrogen resources utilization. For higher coal resource utilization and lower carbon emission, this paper proposes a novel methanol production process from coal gasification integrated with coal coking. This process consists of the units of coal gasification, coking, coke gasification, dry methane reforming, and methanol synthesis. Coke gasification transforms the low-valued coke to high-valued chemicals and makes the process suitable for market variation. DMR converts methane and CO2 into syngas, increasing the overall resource utilization efficiency. This integrated process has the advantages of higher valued products and larger methanol productivity. According to the simulation and detailed techno-economic analysis, the new process has a much higher carbon utilization efficiency of 51.6%, compared to 37.3% of the single coal to methanol (CTM) process, and the corresponding CO2 emission is reduced by 34.6%. The energy efficiency of the CGCTM process is 62%, which is about 21.6% higher than that of CTM process. As for economic benefits, the internal rate of return for the new process is 22.5%, much higher than 15.3% of the current CTM process. Highlights: An integrated process of coal gasification and coking to methanol production was proposed. The new process is suitable for market variation and can enhance the flexibility of the system. The new process has much higher carbon utilization efficiency and lower CO2 emission. The new process will show the economic advantages in the era of high carbon tax.